Analisis pendekatan Adlerian dalam konseling kelompok untuk optimalisasi potensi diri siswa - Zadrian Ardi; Neviyarni Neviyarni; Yeni Karneli; Netrawati Netrawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
Students have a variety of potentials that need to be explored and developed. The process of self-development is a necessity, which the school is an institution that is given the task of these efforts through counselors. However, various obstacles actually arise in the process throughout the range of student development. This is a tough challenge for counselors in alleviating developmental problems and optimizing the abilities and potential of students through counseling services, one of which is group counseling. The Adlerian approach is one approach in group counseling that is popular in practice. In this article, we will discuss the analysis of the contribution of values contained in the Adlerian approach that is implemented in group counseling services in order to optimize students' self-potential.